Shaping romance : interpretation, truth, and closure in twelfth-century French fictions - Bruckner, Matilda Tomaryn (Middle Ages series., 1993)
Examines a set of five twelfth-century romance texts--complete and fragmentary, canonical and now neglected, long and short--to map out the characteristics and boundaries of the genre in its formative period.